Update on genetics and diabetic retinopathy - Hampton BM (Dove Medical Press, 2015)
Blake M Hampton,1 Stephen G Schwartz,1 Milam A Brantley Jr,2 Harry W Flynn Jr1 1Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA; 2Department of Ophthalmology, Vanderbilt Eye Institute, Nashville, TN, USA Abstract: Clinical risk factors for diabetic retinopathy (DR), such as duration of disease and degree of glucose control, do not adequately predict disease progression in individual patients, suggesting the presence of a genetic component. Multiple smaller studies have investigated genotype–phenotype correlations in genes encoding vascular endothelial growth factor, aldose reductase, the receptor for advanced glycation end products, and many others. In general, reported results have been conflicting, due to factors including small sample sizes, variations in study design, differences in clinical end points, and underlying genetic differences between study groups. At this time, there is no confirmed association with any risk allele reported. As we continue to collect data from additional studies, the role of genetics in DR may become more apparent. Keywords: diabetic retinopathy, genetics, single nucleotide polymorphism, genome-wide association study